Digitalisasi Sistem Pembayaran Pajak Kendaraan Bermotor pada Badan Pendapatan Daerah Provinsi Maluku - , Enjelika Katerina Hitipeuw; Zainal Abidin Rengifurwarin; Stanislaus Kostka Ohoiwutun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes the digitalization of the motor vehicle tax payment system at the Regional Revenue Agency of Maluku Province. The research is motivated by the need to improve regional tax services in an archipelagic province where geographical distance, manual administrative procedures, uneven internet access, and limited service points often increase the compliance cost of taxpayers. This study employed a descriptive qualitative method with data collected through passive participant observation, in-depth interviews, and documentation. Nine informants were selected purposively from the Regional Revenue Agency, related service units, and taxpayers. The analysis used an interactive qualitative model and was guided by program effectiveness dimensions, namely target accuracy, program socialization, goal achievement, and monitoring and evaluation, as well as implementation factors consisting of communication, resources, disposition, and bureaucratic structure. The findings show that the digitalization of motor vehicle tax payments has generally operated effectively by expanding service access, reducing waiting time, improving administrative transparency, and strengthening monitoring through coordinated institutional mechanisms. Nevertheless, the effectiveness of the system is still constrained by uneven internet infrastructure, limited budget capacity, and the persistence of hybrid service practices in several areas. The study implies that digital tax services in archipelagic regions require not only technological platforms, but also sustained socialization, human resource development, inter-agency coordination, and equitable digital infrastructure.